2020
DOI: 10.3390/rs12233871
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of IMERG-V06, TRMM-3B42V7, SM2RAIN-ASCAT, and PERSIANN-CDR Precipitation Products over the Hindu Kush Mountains of Pakistan, South Asia

Abstract: In this study, the performances of four satellite-based precipitation products (IMERG-V06 Final-Run, TRMM-3B42V7, SM2Rain-ASCAT, and PERSIANN-CDR) were assessed with reference to the measurements of in-situ gauges at daily, monthly, seasonal, and annual scales from 2010 to 2017, over the Hindu Kush Mountains of Pakistan. The products were evaluated over the entire domain and at point-to-pixel scales. Different evaluation indices (Correlation Coefficient (CC), Root Mean Square Error (RMSE), Bias, and relative B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 56 publications
4
22
0
Order By: Relevance
“…Calibrated models could misrepresent the uncertainty as the calibration process may disguise such uncertainty in forcing dataset (Biemans et al., 2009; Schmied et al., 2014). Precipitation is amongst the most important forcing data that is subject to major uncertainties due to climate and topographic complexities (Faridzad et al., 2018; Hamza et al., 2020; Henderson‐Sellers et al., 1993; Tang et al., 2018) and directly affects water balance (Bárdossy & Das, 2008; Nilsson et al., 2005; Wang et al., 2016). Particularly for the MRB, studies have suggested that over 65% of the streamflow variations in parts of the basin can be attributed to the variations in precipitation alone (Fan & He, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Calibrated models could misrepresent the uncertainty as the calibration process may disguise such uncertainty in forcing dataset (Biemans et al., 2009; Schmied et al., 2014). Precipitation is amongst the most important forcing data that is subject to major uncertainties due to climate and topographic complexities (Faridzad et al., 2018; Hamza et al., 2020; Henderson‐Sellers et al., 1993; Tang et al., 2018) and directly affects water balance (Bárdossy & Das, 2008; Nilsson et al., 2005; Wang et al., 2016). Particularly for the MRB, studies have suggested that over 65% of the streamflow variations in parts of the basin can be attributed to the variations in precipitation alone (Fan & He, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that these most recent global SRPs are freely available at precise spatial and temporal resolutions, their performance differs from one location to the next across the globe [12,13]. The literature review revealed that the performance evaluation of SRPs is essential before their direct application in any region [7,[14][15][16]. In this regard, several researchers have evaluated the accuracy of different SRPs in several countries-for instance, in America [17], Brazil [18], China [19][20][21], Italy [22], Iran [23], Malaysia [24], Pakistan [14], Taiwan [25], and Saudi Arabia [26].…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation data with high accuracy and high spatial resolution play significant roles in forcing local and global climate models and hydrological and ecological models. Studies have shown that the performance of IMERG products is better than those of some other satellite-based precipitation datasets [25,50]. However, in some basins and localized areas, the IMERG products are still too coarse to be applied.…”
Section: Discussionmentioning
confidence: 99%